An Efficacy Study of the Open Hands Financial Education Program - Coggin, Wynn (Christian higher education, 2025)
Open Hands is a six-week voluntary program that aims to increase financial literacy among Christian college juniors and seniors. This study, conducted at two Christian institutions of higher education in the Midwest and Southeast United States, tested the efficacy of the Open Hands finance program. Using a randomized subject, pretest-posttest control group design, the researchers measured the effect of the Open Hands finance program on the posttest scores of the experimental group compared to the control group while controlling for pretest scores. An ANCOVA was used to analyze the results from the 89 participants’ tests. The independent variable of the Open Hands program was significant (F = 6.073, p = .016), with the average participant in the experimental group increasing their score on the 13-question test by 2.19 correct answers. Additionally, in the pretest phase, business majors were found to have significantly higher financial literacy than psychology majors, and the academic major category did not have a significant impact on posttest scores. The significant increase in posttest scores among the experimental group shows the potential benefit Open Hands can have for Christian college students. The true randomized design for this experiment along with the size and scope of the experiment suggests a reliable outcome for Christian college administrators should they administer the Open Hands program in a similar setting.